Gringuinho: a Short Story that Summarizes Samuel Rawet's Poetics - Franco Junior, Arnaldo [UNESP]; Aparecido Valentin, Leandro Henrique (Univ Federal Minas Gerais-ufmg, 2015)
This article analyzes Gringuinho, by Samuel Rawet, focusing on the relationship between Rawet's crafting of the short story under study and the adverse experience of the main character, a Jewish boy who is an immigrant and lives in Brazil. Based both on the analysis and interpretation developed, this paper claims Gringuinho is a short story that summarizes the core aspects of Samuel Rawet's poetics.
Keywords: Short Story; Poetics; Samuel Rawet